PENGARUH PENGELOLAAN MODAL KERJA (SIKLUS KONVERSI KAS) TERHADAP PROFITABILITAS PERUSAHAAN (ROA) - Muhammad Fauzan; Herry Laksito (Diponegoro Journal of Accounting, 2015)
The management of working capital and return on assets (ROA) are two of several factors to determine the level of efficiency of the company in its operational activities. The samples in this research were taken from manufacturing companies that have been listed on the Indonesia Stock Exchange from 2011 - 2013, with the problem studied is the management of working capital which consists of three sub-variables: Days of Sales Outstanding (X1), Days of Inventory Outstanding (X2), and Days of Payable Outstanding (X3) as the independent variables and Return On Asset (Y) as the dependent variable.To analyze Days of Sales Outstanding (X1), Days of Inventory Outstanding (X2), and Days of Payable Outstanding (X3) on Return On Asset (Y), the author uses descriptive analysis, a classic assumption test, multiple linear regression, correlation coefficient, coefficient of determination, f test, and t test.Based on statistical analysis of coefficient of determination test indicated that there were influence between Days of Sales Outstanding, Days of Inventory Outstanding and Days of Payable Outstanding on Return on Assets of 9.1% while the remaining 90.9% was influenced by other factors.While testing the hypothesis with t test showed thatReturn On Asset affected by variable Days of Sales Outstanding. Sub Days of Inventory Outstanding variable has no effect on Return On Asset. Sub variableDays of Payable Outstanding affect on Return On Asset. While f test showed that the sub-variableDays of Sales Outstanding, Days of Inventory Outstanding and Days of Payable Outstanding has effect on the Return On Asset.